2023
DOI: 10.3390/en16135202
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Control Unit for the Angle of Attack of a Vertically Axial Wind Turbine

Abstract: This article presents the possibility of increasing the efficiency of a vertical-axis wind generator through the introduction of an automatic control system for the angle of attack of the blades. The calculation of the optimal position of the wind turbine blades for the maximum generation of electrical energy is given, and a developed scheme for controlling the blades using the sensors of the angular speed of rotation of the wind wheel by the anemometer and the current position of the blades is presented. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Combined, wind and solar energy provided a record fifth of the EUs electricity (22.3%)-a contribution larger for the first time than either nuclear (21.9%) or gas (19.9%) generation [6]. According to the Union of the Electricity Industry, Eurelectric, two-thirds of the electricity generated in Europe in the first half of 2023 is carbon-free [7]. The share of renewable energy sources is 40% of the total production, while electricity generation based on fossil fuels has fallen by 18% [8].…”
Section: Introductionmentioning
confidence: 99%
“…Combined, wind and solar energy provided a record fifth of the EUs electricity (22.3%)-a contribution larger for the first time than either nuclear (21.9%) or gas (19.9%) generation [6]. According to the Union of the Electricity Industry, Eurelectric, two-thirds of the electricity generated in Europe in the first half of 2023 is carbon-free [7]. The share of renewable energy sources is 40% of the total production, while electricity generation based on fossil fuels has fallen by 18% [8].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the vertical-axis wind generator configurations can be found in [69], where the main problems of the available technologies are highlighted. As concerns the active control of wind generator performance by shaping the blades of the turbine, it starts from accurate simulations [70], which allows for strategies based on intelligent control aimed at fixing specific angles of attack [71] or blade pitching [72].…”
mentioning
confidence: 99%